Unraveling Interactions of the Necrotrophic Fungal Species Botrytis cinerea With 1-Methylcyclopropene or Ozone-Treated Apple Fruit Using Proteomic Analysis - Testempasis, Stefanos; Tanou, Georgia; Minas, Ioannis; Samiotaki, Martina; Molassiotis, Athanassios; Karaoglanidis, Georgios (Frontiers in Plant Science, 2021)
Gray mold caused by the necrotrophic fungus Botrytis cinerea is one of the major postharvest diseases of apple fruit. The exogenous application of 1-methylcyclopropene (1-MCP) and gaseous ozone (O 3) is commonly used to ensure postharvest fruit quality. However, the effect of these treatments on the susceptibility of apple fruit to postharvest pathogens remains largely unknown. Herein, the effect of O 3 and 1-MCP treatments on the development of gray mold on apple fruit (cv. “Granny Smith”) was investigated. Artificially inoculated apple fruits, treated or not with 1-MCP, were subjected for 2 months to cold storage [0°C, relative humidity (RH) 95%] either in an O3-enriched atmosphere or in a conventional cold chamber. Minor differences between 1-MCP-treated and control fruits were found in terms of disease expression; however, exposure to ozone resulted in a decrease of disease severity by more than 50% compared with 1-MCP-treated and untreated fruits. Proteomic analysis was conducted to determine proteome changes in the mesocarp tissue of control and 1-MCP- or O3-treated fruits in the absence or in the presence of inoculation with B. cinerea. In the non-inoculated fruits, 26 proteins were affected by 1-MCP, while 51 proteins were altered by ozone. Dynamic changes in fruit proteome were also observed in response to B. cinerea. In O3-treated fruits, a significant number of disease/defense-related proteins were increased in comparison with control fruit. Among these proteins, higher accumulation levels were observed for allergen, major allergen, ACC oxidase, putative NBS-LRR disease resistance protein, major latex protein (MLP)-like protein, or 2-Cys peroxiredoxin. In contrast, most of these proteins were down-accumulated in 1-MCP-treated fruits that were challenged with B. cinerea. These results suggest that ozone exposure may contribute to the reduction of gray mold in apple fruits, while 1-MCP was not effective in affecting this disease. This is the first study deciphering differential regulations of apple fruit proteome upon B. cinerea infection and postharvest storage treatments, underlying aspects of host response related to the gray mold disease.